Pengaruh Suhu dan Lama Penyimpanan Urine Pasien Infeksi Saluran Kemih terhadap Jumlah Bakteri - Aziza, Vidayatul; Rini, Chylen S.; Aliviameita, Andika; Rohmah, Jamilatur (Universitas Sam Ratulangi, 2025)
Abstract: Urinary tract infection (UTI) is caused by the growth of microorganisms in the urinary tract. The gold standard in diagnosing UTI is bacterial count. This study aimed to determine the effects of temperature and storage time for urine of patients with UTI on the number and the species of bacteria, which is important in supporting the diagnosis of UTI. This was a laboratory and experimental study using accidental sampling techniques in accordance with the inclusion criteria. The results showed that at room temperature (20-25oC) the number of bacteria increased faster and was higher than the number of bacteria stored at cold temperature (2-8oC). The number of bacterial colonies was the highest at storage time of 5 hours (5.3x104 CFU/ml) meanwhile the lowest was in fresh urine (3.4 x 104 CFU/ml). The Friedman test showed that there was an effect of temperature and storage time for urine of patients with UTI on the number of bacteria with a sig p-value of 0.001 (p<0.05). In conclusion, the average number of bacteria at room temperature (20-25oC) increased faster than at cold temperature (2-8oC) during a storage time of five hours. Keywords: urinary tract infection; number of bacteria; storage time; urine Abstrak: Infeksi saluran kemih (ISK) diakibatkan adanya pertumbuhan mikroorganisme di dalam saluran kemih. Baku emas dalam mendiagnosis ISK ialah menghitung jumlah bakteri dalam urin. Penelitian ini bertujuan untuk mengetahui pengaruh suhu dan lama penyimpanan urin pada pasien ISK terhadap jumlah dan jenis bakteri yang penting dalam menunjang diagnosis ISK. Penelitian ini menggunakan metode eksperimental laboratorik dengan teknik pengambilan sampel accidental sampling sesuai dengan kriteria inklusi. Hasil penelitian mendapatkan bahwa pada suhu ruang (20-25oC) jumlah bakteri meningkat lebih cepat dan lebih banyak dibandingkan jumlah bakteri pada suhu dingin (2-8oC). Rerata jumlah koloni bakteri yang tertinggi yaitu sebesar 5,3x104 CFU/ml didapatkan pada waktu penyimpanan 5 jam di suhu ruang, dan yang terendah pada urin segar sebesar 3,4 x 104 CFU/ml. Hasil uji Friedman menunjukkan terdapat pengaruh suhu dan lama penyimpanan urin pada pasien ISK terhadap jumlah bakteri dengan nilai p=0,001 (p<0,05). Simpulan penelitian ini ialah rerata jumlah bakteri pada suhu ruang (20-25oC) meningkat lebih cepat dibandingkan pada suhu dingin (2-8oC) selama waktu penyimpanan 5 jam. Kata kunci: infeksi saluran kemih; jumlah bakteri; lama penyimpanan; urin